Effect of particle size, shape, and weight percentage of hydroxyapatite (HA) on rheological behaviour of polycaprolactone/hydroxyapatite (PCL/HA) composites / Zulaisyah Laja Besar and Suffiyana Akhbar - Laja Besar, Zulaisyah; Akhbar, Suffiyana (Universiti Teknologi MARA, 2021)
The aim of this study is to investigate the influence of hydroxyapatite's (HA) particle size, shape, and variation of HA weight percentage on the rheological behaviour of polycaprolactone/hydroxyapatite (PCL/HA) composite. The composite was produced by melt blending process using a single screw extruder assisted with an ultrasonic wave with varied HA weight content (0 wt.%, 10 wt.%, 20 wt.%, 30 wt.% and 40 wt.%). Two types of HA were used, which are needle shape (HAN) and irregular shape (HAS). The rheological behaviour of the PCL/HA composite was investigated through the melt flow index (MFI) test at a varied temperature of 100, 110, and 120 °C. The result indicated that an increase of HA content decreases the MFI values of the PCL/HA composite. At similar content of HA, PCL/HAN composite has higher activation energy with lower MFI values compared to PCL/HAS composite. In conclusion, this study concluded that the particle size, shape, and weight percentage of HA significantly affect the rheological behaviour of PCL/HA composites.